Optimalisasi Prestasi Kerja Karyawan dengan Menggunakan Analisis SEM PLS - Yanti, Novi; Mallisza, Danyl; Mariandi, Reski (SAFE-Network, 2022)
PT. Kereta Api Indonesia (Persero) Regional Division II West Sumatra is one of the State-Owned Enterprises (BUMN) engaged in rail transportation services. The company is very concerned about improving employee performance. Factors that affect achievement are career planning, work environment and work stress. Career planning is an opportunity created by the company in developing the talents possessed by its employees. This study aims to analyze the influence of these factors on employee performance in optimizing company functions so that they improve better. The data population processed in the study amounted to 510 people and the sample used was 83 people who were processed using the Slovin formula. The analytical method used is Partial Least Square (PLS) Structural Equation Model (SEM) in measuring the level of relationship of each variable with its construct indicators. The results obtained are the contribution of career planning, career environment, and work stress to employee performance of 46.5%, with 53.5% being influenced by other variables outside of this study. So that this research can be used as an indicator in optimizing employee performance.